Impact of Social Determinants of Health on Follow-up for Neonates Requiring Neurocritical Care - Eiler, Isabella; Boyd, Lakeisha; Klitzman, Melissa; Majmudar-Sheth, Bittu; Stefanescu, Beatrice M. (American Journal of Perinatology, 2024)
This study aimed exploration of associations of social determinants of health (SDH) with attrition rates of neurocritical care graduates at follow-up.An observational retrospective cohort study was conducted to evaluate the attrition rates of an infant's first appointment scheduled with the NeuroNICU follow-up clinic in correlation with SDH.The “No Show” group was more likely to have unemployed (p = 0.014), black or multiracial mothers (p = 0.005), public insurance (p < 0.001), lower gestational age (p < 0.001), live further from the clinic (0.011), and a lower zip code-associated income (p = 0.008). After controlling for driving time, race, and education, infants who had private insurance were 2.268 times more likely to attend their follow-up visit when compared with infants who had public insurance (p = 0.014).A significant SDH-related difference existed among the “Show” and “No Show” groups. Identifying these factors during neonatal intensive care unit (NICU) admission can facilitate targeted support for families while inpatient and promote improved outpatient follow-up.
Keywords: attrition; infant follow-up; social determinants of health